Resonance modes of tall plasmonic nanostructures and their applications for biosensing - Soehartono, Alana M. (2021)
The collective oscillation of plasmons in metallic nanostructures generates localized surface plasmons (LSP), which are responsive to their surrounding dielectric environment and can be used for low-cost, label-free sensing platforms. However, the inherently short evanescent decay field saturates the optical response within 10-30 nm of the metal surface, hindering multi-layered functionalization strategies typically used for specific binding due to its limited surface proximity. In this work, we propose the use of tall nanostructures to engineer the plasmonic response for biosensing applications. The resonance mode characteristics are investigated, where the emergence of hybrid modes is found to arise from the decoupling of localized plasmon modes at increasing antenna height. Using high aspect ratio plasmonic nanostructures, we demonstrate its viability with up to 4.3 × higher sensitivity and 18.4 × higher figure of merit within the visible range. Coupled with a cost-effective fabrication method, the height provides an additional degree of freedom for tailoring the optical spectrum.